Perbedaan Pergeseran Angulasi Horizontal pada Teknik Radiografi Periapikal terhadap Jumlah dan Tipe Saluran Akar Premolar Pertama Rahang Atas - Widi Hanifah; Annisa Putri; Basma Prakosa; Ainin Fitriyah; Yeni Puspitasari; Catur Septommy (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2026)
Background: Maxillary first premolars are teeth that have varied root canal morphology. The periapical radiographic examination can help identify morphological variations of the root canals. This study aims to determine the difference in the horizontal angulation shift to its number and type of root canals. Methods: The design of study was true experimental using 6 samples of the extracted maxillary first premolars. Each tooth was taken five times with horizontal angulation 0o, 10o, 20o, 30o, and 40o. The data obtained were tested with Cohen's Kappa to see the level of agreement. Then analyzed with the Friedman test to prove the hypothesis. Results: Cohen's Kappa significance value is 0.001. The significant value of the Friedman test is 0.027 Asymp Sig. (<0.05). Conclusion: There is an influence of changes in horizontal angulation in analyzing the root canal morphology of maxillary first premolars. Keywords: Maxillary First Premolars, Horizontal Angulation, Root Canal Morphology Korespondensi Penulis : Annisa Putri, drg., Sp. RKG, Departemen Radiologi Kedokteran Gigi, Fakultas Kedokteran Gigi, Institut Ilmu Kesehatan Bhakti Wiyata, Kota Kediri, Indonesia, Email: annisa.putri@iik.ac.id